The Hyperobject's Atomization of "Self" in Gravity's Rainbow - T.J. Martinson (Orbit: Writing Around Pynchon, 2015)
This article further inspects the Rocket and Schwarzgerät at the center of Thomas Pynchon’s 'Gravity’s Rainbow '(1974). Though scholars commonly employ the Rocket as a metaphor and symbol by which they analyze plot and characters, I inverse this approach to see what the plot and characters can reveal about the Rocket qua Rocket. Drawing from Object-Oriented Ontology—specifically Timothy Morton’s concept of the “hyperobject,” or an entity that is dispersed through time and space—I claim that the Rocket functions as a hyperobject. The tendency of scholars to avoid a claim of reality towards the Rocket, I argue, is an echo of Western philosophy’s long valorization of the epistemological over the ontological that parallels unavailability with unreality. A reading the Rocket as hyperobject reveals a plot of ontological uncertainty unfolding in the characters’ search for inherently recessive entities.